Long‐term neuropathological and behavioral impairments after exposure to nerve agents. Issue 1 (22nd March 2016) - Aroniadou‐Anderjaska, Vassiliki; Figueiredo, Taiza H.; Apland, James P.; Prager, Eric M.; Pidoplichko, Volodymyr I.; Miller, Steven L.; Braga, Maria F.M.
Abstract : One of the deleterious effects of acute nerve agent exposure is the induction of status epilepticus (SE). If SE is not controlled effectively, it causes extensive brain damage. Here, we review the neuropathology observed after nerve agent‒induced SE, as well as the ensuing pathophysiological, neurological, and behavioral alterations, with an emphasis on their time course and longevity. Limbic structures are particularly vulnerable to damage by nerve agent exposure. The basolateral amygdala (BLA), which appears to be a key site for seizure initiation upon exposure, suffers severe neuronal loss; however, GABAergic BLA interneurons display a delayed death, perhaps providing a window of opportunity for rescuing intervention. The end result is a long‐term reduction of GABAergic activity in the BLA, with a concomitant increase in spontaneous excitatory activity; such pathophysiological alterations are not observed in the CA1 hippocampal area, despite the extensive neuronal loss. Hyperexcitability in the BLA may be at least in part responsible for the development of recurrent seizures and increased anxiety, while hippocampal damage may underlie the long‐term memory impairments. Effective control of SE after nerve agent exposure, such that brain damage is also minimized, is paramount for preventing lasting neurological and behavioral deficits.